MR Neurography and Quantitative Muscle MRI of Parsonage Turner Syndrome Involving the Long Thoracic Nerve - Morena, Jonathan; Tan, Ek T.; Campbell, Gracyn J.; Bhatti, Pravjit; Li, Qian; Geannette, Christian S.; Lin, Yenpo; Milani, Carlo J.; Sneag, Darryl B. (Journal of magnetic resonance imaging, 2024)
Background Parsonage‐Turner syndrome (PTS) is characterized by severe, acute upper extremity pain and subsequent paresis and most commonly involves the long thoracic nerve (LTN). While MR neurography (MRN) can detect LTN hourglass‐like constrictions (HGCs), quantitative muscle MRI (qMRI) can quantify serratus anterior muscle (SAM) neurogenic changes. Purpose/Hypothesis 1) To characterize qMRI findings in LTN‐involved PTS. 2) To investigate associations between qMRI and clinical assessments of HGCs/electromyography (EMG). Study Type Prospective. Population 30 PTS subjects (25 M/5 F, mean/range age = 39/15–67 years) with LTN involvement who underwent bilateral chest wall qMRI and unilateral brachial plexus MRN. Field Strength/Sequences 3.0 Tesla/multiecho spin‐echo T2‐mapping, diffusion‐weighted echo‐planar‐imaging, multiecho gradient echo. Assessment qMRI was performed to obtain T2, muscle diameter fat fraction (FF), and cross‐sectional area of the SAM. Clinical reports of MRN and EMG were obtained; from MRN, the number of HGCs; from EMG, SAM measurements of motor unit recruitment levels, fibrillations, and positive sharp waves. qMRI/MRN were performed within 90 days of EMG. EMG was performed on average 185 days from symptom onset (all ≥2 weeks from symptom onset) and 5 days preceding MRI. Statistical Tests Paired t‐tests were used to compare qMRI measures in the affected SAM versus the contralateral, unaffected side (P < 0.05 deemed statistically significant). Kendall's tau was used to determine associations between qMRI against HGCs and EMG. Results Relative to the unaffected SAM, the affected SAM had increased T2 (50.42 ± 6.62 vs. 39.09 ± 4.23 msec) and FF (8.45 ± 9.69 vs. 4.03% ± 1.97%), and decreased muscle diameter (74.26 ± 21.54 vs. 88.73 ± 17.61 μm) and cross‐sectional area (9.21 ± 3.75 vs. 16.77 ± 6.40 mm2). There were weak to negligible associations (tau = −0.229 to <0.001, P = 0.054–1.00) between individual qMRI biomarkers and clinical assessments of HGCs and EMG. Data Conclusion qMRI changes in the SAM were observed in subjects with PTS involving the LTN. Level of Evidence 2 Technical Efficacy Stage 1